2015
DOI: 10.1097/scs.0000000000001886
|View full text |Cite
|
Sign up to set email alerts
|

Orthoptic Sequelae Following Conservative Management of Pure Blowout Orbital Fractures

Abstract: The aim of this study was to prospectively assess the prevalence of orthoptic anomalies following conservative management of pure blowout orbital fractures and to evaluate their clinical relevance. Clinical and radiologic data of patients with unilateral conservatively managed pure blowout orbital fractures with a minimum follow-up of 6 months were reviewed. Eligible patients were contacted and invited to undergo an extended ophthalmologic examination as follows: distance and near visual acuities, Hertel exoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Residual diplopia in conservatively treated patients is reported globally, with a significant range, from 15% to 82%. 1 Independent of the type of injury, the strabismus is likely to change in the first weeks to months as edema resolves 13 (Case 3); 7 days to 10 days after trauma, examination is performed more easily because the initial edema often is resolved partially or mostly. Through orthoptic examination, it can be determined if and to what degree diplopia is improved spontaneously and orbital reconstruction may be prevented.…”
Section: Timing and Frequency Of Orthoptic Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Residual diplopia in conservatively treated patients is reported globally, with a significant range, from 15% to 82%. 1 Independent of the type of injury, the strabismus is likely to change in the first weeks to months as edema resolves 13 (Case 3); 7 days to 10 days after trauma, examination is performed more easily because the initial edema often is resolved partially or mostly. Through orthoptic examination, it can be determined if and to what degree diplopia is improved spontaneously and orbital reconstruction may be prevented.…”
Section: Timing and Frequency Of Orthoptic Examinationmentioning
confidence: 99%
“…There is no real consensus with regard to standardized examination or protocolled treatment to determine either the necessity or type of treatment. 1 Surgical indication, meaning possible orbital repair surgery, is predicated on criteria, such as enophthalmos, restriction of extraocular muscles, type and size of the fracture's defect, degree of diplopia, and clinicoradiological findings. 1e3…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, studies have been primarily focused on clinical prognostic factors and have reported severe diplopia immediately after trauma and/or persisting at 10 to 14 days and patient age as the most important predictors of the decision for surgical exploration. 1,3,4,9,10,13,14,21,24,25,40 These elements strongly contributed to the generally accepted approach to wait for a 1-to 2-week observation period before deciding on a definitive management strategy, with the exception of pediatric fractures. By contrast, only a few studies have reported on the predictive value of initial diplopia for persistent long-term annoying diplopia.…”
Section: E4mentioning
confidence: 99%
“…By contrast, only a few studies have reported on the predictive value of initial diplopia for persistent long-term annoying diplopia. 1,3,9,10,24,25 The occurrence of the development of enophthalmos has been mainly related to orbital volume increase rather than fracture size. 26,27 A few studies have reported on fracture size measured on CT scan images and/or IRM changes (morphologic and positional) as radiologic predictors for the decision for surgery and persistence of diplopia and/or enophthalmos in patients with BOFs.…”
Section: E4mentioning
confidence: 99%
See 1 more Smart Citation